Fermentation and biochemical engineering handbook : (Noyes Publications, 1997)
The second edition of this handbook, like the first edition, is a well-rounded, up-to-date handbook of fermentation and biochemical engineering, presenting the latest techniques for the commercial production of chemicals and pharmaceuticals via fermentation. Emphasis is given to unit operations - fermentation, separation, purification, and recovery. Principles, process design, and equipment are detailed. The environmental aspects are also covered. The practical aspects of development, design, and operation are stressed, and some theory is included to provide the necessary insight for a particular operation. Problems addressed are the collection of pilot data, choice of scale-up parameters, selection of the right piece of equipment, pinpointing of likely trouble spots, and methods for troubleshooting. The text, written from a practical and operating viewpoint, will assist development, design, engineering and production personnel in the fermentation industry. The contributors were selected based on their industrial background and orientation.